2019
DOI: 10.13057/biodiv/d200943
|View full text |Cite
|
Sign up to set email alerts
|

Traditional ecological knowledge and biodiversity conservation: the medicinal plants of the Dayak Krayan people in Kayan Mentarang National Park, Indonesia

Abstract: Abstract. Susanti R, Zuhud EAM. 2019. Traditional ecological knowledge and biodiversity conservation: the medicinal plants of the Dayak Krayan people in Kayan Mentarang National Park, Indonesia. Biodiversitas 20: 2764-2779. Traditional ecological knowledge and biodiversity conservation can support one another for management of national parks in Indonesia as some such areas established in customary areas. This quantitative ethnobotany study aims to find the correlation of traditional ecological knowledge of med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
5
25
0
3
Order By: Relevance
“…Figure 2 displays the life form of medicinal plants. These results are the same as the findings in many other studies which also reported that medicinal plant species generally have habitus herbs, trees, and shrubs [10,11,12,13].…”
Section: Species Richness and Abundance Of Medicinal Plantssupporting
confidence: 91%
“…Figure 2 displays the life form of medicinal plants. These results are the same as the findings in many other studies which also reported that medicinal plant species generally have habitus herbs, trees, and shrubs [10,11,12,13].…”
Section: Species Richness and Abundance Of Medicinal Plantssupporting
confidence: 91%
“…Such areas are less suitable for agriculture or plantation expansions 29 . Besides that, the traditional Dayak communities living in Kayan Mentarang still value natural ecosystem highly and that helps to protect them from external influences 55 , 56 . Management by indigenous peoples or local communities can be a factor that improves the effectiveness of conservation area 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to using dyes, craftsmen also add a natural adhesive obtained from the Euphorbiaceae family member with the aim of maintaining a longer color quality because the colors are perfectly glued on threads or other craft items. (Susanti et al 2019): 1. unspecified medicinal disorder 2. Abnormalities 3. blood system disorder 4. circulatory system disorder 5.…”
Section: Plants As Source Of Cosmetics Coloring (Dyes) Materials and Pesticidesmentioning
confidence: 99%